2009
DOI: 10.1111/j.1744-7909.2009.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Range Expansion and Glacial Endurance of Potentilla glabra (Rosaceae) in the Qinghai‐Tibetan Plateau

Abstract: To date, little is still known about how alpine species occurring in the Qinghai-Tibetan Plateau (QTP) responded to past climatic oscillations. Here, by using variations of the chloroplast trnT-L, we examined the genetic distribution pattern of 101 individuals of Potentilla glabra, comprising both the interior QTP and the plateau edge. Phylogenetic and network analyses of 31 recovered haplotypes identified three tentative clades (A, B and C). Analysis of molecular variance (amova) revealed that most of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
72
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 46 publications
15
72
3
Order By: Relevance
“…A high level of haplotype diversity within Z. xanthoxylem was also supported by the AMOVAs, which showed that a large percentage of the variation was explained by differences within populations ( Table 3). Patterns of higher haplotype diversity within populations are consistent with those found in other outbreeding species (Hamrick and Godt 1996;Nybom and Bartish 2000;Wang et al 2009b). However, due to the slow evolutionary rate of the chloroplast genome (Zurawski et al 1984), the observed haplotype diversity may reflect historical patterns.…”
Section: Hypothetical Phylogeographical History Of Z Xanthoxylumsupporting
confidence: 80%
See 1 more Smart Citation
“…A high level of haplotype diversity within Z. xanthoxylem was also supported by the AMOVAs, which showed that a large percentage of the variation was explained by differences within populations ( Table 3). Patterns of higher haplotype diversity within populations are consistent with those found in other outbreeding species (Hamrick and Godt 1996;Nybom and Bartish 2000;Wang et al 2009b). However, due to the slow evolutionary rate of the chloroplast genome (Zurawski et al 1984), the observed haplotype diversity may reflect historical patterns.…”
Section: Hypothetical Phylogeographical History Of Z Xanthoxylumsupporting
confidence: 80%
“…These distinctive haplotypes was generated due to the topographic characteristics, recent population expansion or population expansion and contraction constantly by the climate volatility in East regions. This pattern happened in previous studies (Chen et al 2013;Wang et al 2009b). Table 1 for geographical details Although this study was conducted across many regions, including deserts, mountains ranges and so on, no clear effect of these acting as significant barriers was detected, as manifested in the lack phylogeographical structure.…”
Section: Hypothetical Phylogeographical History Of Z Xanthoxylumsupporting
confidence: 60%
“…Our permutation tests also indicated that N ST was significantly higher than G ST , suggesting the presence of a strong structure across the distribution of O. thoroldii. In addition, although the cpDNA haplotype richness was very low, only seven haplotypes were found in total, it was noteworthy that high levels of total and within population diversities were detected in O. thoroldii Wang et al, 2009b). Although seven nrITS sequence types were distributed across the entire distribution region, their phylogenetic relationships were not well resolved.…”
Section: Genetic Structurementioning
confidence: 92%
“…Another example shows that Potentilla glabra lodd. (Rosaceae) survived in two regions located in both the interior and edge of the QTP (Wang et al, 2009b). These studies suggest that many alpine plants in the QTP have a diverse phylogeographic history.…”
Section: Introductionmentioning
confidence: 96%